Translation of The Article by Titled “Osh City and Throne of Sulaiman” into Kyrgyz Language - Zuuridinov, Oskonbay (Scientific Journal of Faculty of Theology, 2021)
This article included historical information about Osh city and Sulaiman mountain may have been written by Ahlullah Hayrullah oglu. The autor criticized mythical beliefs about Osh city and Sulaiman mountain because of he adopted jadidism. This article is published in journal of Shuro in 1913 on 1 august as 14 pieces.